Worldviews in transition : the changing nature of the Lake Nipigon Anishinabek Metis - McGuire, Patricia D. (2003)
In Northwestern Ontario (NWO) there is a need to assure a more complete understanding of the Indigenous voice. The researcher, who examined existing theories and research methodologies in sociology, determined that these frameworks of the world have difficulty conceptualizing Indigenous-based cultural worldviews. This impedes adequate awareness and understanding of this population. This study was an exploration into the need to develop alternatives to the standard sociological theories. The researcher argued that it is only by exploring alternative theoretical frameworks that we can develop and create awareness and understanding of other cultures. An Indigenous, culturally based theoretical framework was used to explore the personal standpoint of the Lake Nipigon Anishinabek Metis, as represented by the writings of one of its Elders. The Anishinabek Metis worldview and ways of learning about the world was revealed and described in these stories. This way of learning about the world through stones and story telling has been documented by other disciplines such as anthropology. What is unique about this study is that the researcher is interpreting these stories from her culturally based vantage point The researcher uses her subjectivity and experience to assist in the interpretation process of the stories told. It is intended that this, utilizing an Indigenous-based theoretical framework and examining it by using an Indigenous voice will create an awareness and understanding of this population in NWO.